2020
DOI: 10.1002/nau.24486
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a new β3‐adrenoceptor agonist, vibegron, on neurogenic bladder dysfunction and remodeling in mice with spinal cord injury

Abstract: Aims: To examine vibegron effects on lower urinary tract dysfunction (LUTD) in mice with spinal cord injury (SCI). Methods: Female mice underwent Th8-9 spinal cord transection and were orally administered vehicle or vibegron after SCI. We evaluated urodynamic parameters at 4 weeks after SCI with or without vibegron. Fibrosis-and ischemia-related messenger RNA (mRNA) and protein levels of collagen and elastin were measured in bladders of vehicle-and vibegron-treated SCI mice, and spinal intact mice. Results: No… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The vast majority of the analyzed reports, 74%, use spinal cord injury as an NDO model ( Figure 2 B). From these publications, 59% report complete transection of thoracic segments to induce SCI [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 38 , 39 , 43 , 44 , 46 , 48 , 49 , 50 , 55 , 57 , 62 , 63 ], followed by spinal contusion (13%). The use of spinal hemisections was less frequent (10%) [ 42 , 47 , 52 ], as were spinal compressions (8%) [ 32 , 36 , 54 , 56 ] and other SCI methods (10%) [ 41 , 51 , 53 , 58 ] ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The vast majority of the analyzed reports, 74%, use spinal cord injury as an NDO model ( Figure 2 B). From these publications, 59% report complete transection of thoracic segments to induce SCI [ 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 38 , 39 , 43 , 44 , 46 , 48 , 49 , 50 , 55 , 57 , 62 , 63 ], followed by spinal contusion (13%). The use of spinal hemisections was less frequent (10%) [ 42 , 47 , 52 ], as were spinal compressions (8%) [ 32 , 36 , 54 , 56 ] and other SCI methods (10%) [ 41 , 51 , 53 , 58 ] ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Most of the studies reporting urodynamic recordings used awake cystometry as the recording method (37%) [ 31 , 32 , 33 , 34 , 35 , 38 , 39 , 42 , 46 , 47 , 48 , 52 , 56 , 59 , 63 , 68 , 70 , 71 ]. Cystometry under anesthesia represented 26% of studies, with 16% using urethane delivered via subcutaneous [ 26 , 27 , 28 , 37 , 41 , 43 , 51 ] or intraperitoneal injection [ 57 ], 8% using zolotyl [ 53 , 58 , 61 , 74 ], and 2% referring the use of chloral hydrate as anesthetic [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that SCI induces bladder remodeling associated with tissue fibrosis, which may adversely affect smooth muscle function and the bladder capacity to micturition properly, resulting in a low voiding efficiency and reduced compliance [ 34 , 35 ]. In this study, compared with fibrosis of the bladder wall in the SCI group, the ADSC group showed normal morphology of the bladder wall and reduced tissue fibrosis as demonstrated by downregulation of type 1 collagen.…”
Section: Discussionmentioning
confidence: 99%
“…25 Furthermore, Gotoh et al reported that vibegron could indirectly suppress C-fiber bladder afferent activity and reduce DO by acting on both nerves and muscles in mice with spinal cord injury. 26 Nantel et al reported that the b3-adrenoceptor is resistant to long-term desensitization, which might have promoted the sustained efficacy of vibegron. 27 These findings suggest that vibegron could be an alternative treatment option for antimuscarinic-resistant neurogenic bladder dysfunction.…”
Section: Discussionmentioning
confidence: 99%